2021
DOI: 10.1515/tjb-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Total cholesterol/HDL cholesterol ratio and monocyte/HDL cholesterol ratio are related with subclinical hypothyroidism in polycystic ovary syndrome

Abstract: Objectives There is an association between serum thyrotropin (TSH) and lipid profile. However, there is a little information regarding the relation between subclinical hypothyroidism (SCH), atherogenic indices and inflammation in polycystic ovary syndrome (PCOS). Herein, we aimed to evaluate the impact of SCH on lipids and inflammatory markers in newly diagnosed PCOS patients. Methods Two groups were performed for total 99 PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…MHR is known both as a marker of inflammation and as a prognostic factor for cardiovascular diseases. MHR has been studied in many medical diseases [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, there are limited studies in the literature on schizophrenia patients [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…MHR is known both as a marker of inflammation and as a prognostic factor for cardiovascular diseases. MHR has been studied in many medical diseases [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, there are limited studies in the literature on schizophrenia patients [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of TC/HDL or LDL/HDL is the surrogate for ApoB/ApoA 14 . In a study of 99 PCOS patients conducted by Cakir and Simsek, the ratio of TC/HDL was significantly higher 9 . In this study, the ratios of TC/HDL and LDL/HDL were significantly higher in the PCOS group than those in the control group.…”
Section: Discussionmentioning
confidence: 94%
“…Yılmaz et al found that NLR was higher in the PCOS group than that in the control group 17 . Another study reported that NLR was significantly higher 9 . In this study, no significant differences were found for NLR between the PCOS and control groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations